2010
DOI: 10.1002/mame.201000325
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalysis in Polyamide 6.6 Solid‐State Polymerization

Abstract: Solid‐state polymerization (SSP) of a poly(hexamethyleneadipamide) (PA 6.6)/clay nanocomposite system was studied. SSP runs were performed in a fixed‐bed reactor, at temperatures 160–200 °C and reaction times up to 8 h. The influence of clay presence on the PA 6.6 SSP rate constant was herewith quantified for the first time to prove significant acceleration of the SSP process. A catalysis mechanism was suggested, according to which the positive effect of clay is of a synergistic origin attributed to nucleated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Moreover, this η rel increase persisted after the extrusion step for PA 6.6 containing OMT1 and OMT2a and reached up to 75% (Figure 2, post‐extrusion grades). This observed polymerizability enhancement in the presence of nanofillers is in agreement with a recently reported nanocatalysis of PA 6.6 solid‐state polymerization by our group,25, 26 and for the first time it is herewith expanded to the solution melt polymerization process. Based on our suggested mechanism,25–29 nanocatalysis may be attributed to clay action as a substrate to polyamidation, by forming an active intermediate between its SiOH groups and polyamide COOH groups.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, this η rel increase persisted after the extrusion step for PA 6.6 containing OMT1 and OMT2a and reached up to 75% (Figure 2, post‐extrusion grades). This observed polymerizability enhancement in the presence of nanofillers is in agreement with a recently reported nanocatalysis of PA 6.6 solid‐state polymerization by our group,25, 26 and for the first time it is herewith expanded to the solution melt polymerization process. Based on our suggested mechanism,25–29 nanocatalysis may be attributed to clay action as a substrate to polyamidation, by forming an active intermediate between its SiOH groups and polyamide COOH groups.…”
Section: Resultssupporting
confidence: 92%
“…In addition to the aforementioned organoclay hydrophilicity, another feature of these materials that could have also hindered the escape of polycondensation water was their well‐known barrier properties 24, 40. At this point, we should mention that in our recent study,32 such an effect was not found to dominate the SSP reaction rate because a notable catalysis (53% rate increase) in the presence of organoclay was observed, as mentioned in the Introduction. However, in the herewith studied combination of antioxidant and clay, the catalyzing effect was much more intense than in the single clay case (nearly quadruple: a 197% vs 53% rate increase, respectively).…”
Section: Resultsmentioning
confidence: 85%
“…Another additive family that has lately been used extensively for the modification and/or improvement of material properties is that of nanoparticles, such as silica, carbon nanotubes, and clays 24–27. A key feature of these nanosized additives is their recently reported catalytic action during SSP 28–32. Particularly for PA 6,6 SSP, the catalyzing effect of clay was observed, quantified, and interpreted for the first time in our recent work;32 this, thus, promoted nanofiller incorporation not only for the modification and/or improvement of material properties but also for their performance as SSP multifunctional catalysts.…”
Section: Introductionmentioning
confidence: 70%
“…Other researchers have reported increased rates of SSP for their montmorillonite (MMT) nanocomposites. Papaspyrides et al42 reported significant acceleration of the SSP process for their poly(hexamethyleneadipamide; PA 6.6)/clay nanocomposites. They attributed the increased rates to an increased concentration of reactive end groups in the amorphous phase, chain extension by clay SIOH groups, and to thermal protection of the polyamide matrix by the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%